Search trend on nutrition during the COVID-19 pandemic in Brazil: Google trends results (Research, Society and Development, 2021)
Introduction: Google Trends (GT) is a widely used tool for trend research. However, few studies have investigated search trends associating Nutrition themes with COVID-19. Objective:  To investigate the themes involving Nutrition in the period of the COVID-19 pandemic. Methods: Initially, the most searched Nutrition topics on the internet were researched, based on news, publications, and articles. After, the terms were applied to the GT, considering the period from March 1, 2020, to June 20, 2021, and geolocation. The GT data were evaluated by the peaks of interest to the analyzed period. Results: The most cited terms on Google were food safety, vitamin D, herbal medicine, and healthy eating. When applied in the GT, it was observed that the themes of food safety and herbal medicine remained with a high volume of search from the beginning of the pandemic in 2020 to 2021. The terms vitamin D and healthy eating showed peaks of interest at different periods. As for the geolocation, the state of Paraíba was the state that showed the greatest interest among the terms analyzed. Conclusion: The GT has been shown to be a tool to assess social behavior. The subject’s food safety, herbal medicine, and healthy eating showed a high search trend during the COVID-19 pandemic, while the term vitamin D had a peak of interest only at the beginning of the pandemic.